The Influence of Country-Of-Origin and Brand Image on Purchase Intention of Oppo Smartphone With Perceived Quality as Intervening Variables - Setyo Aji Wibowo; Mohamad Rizan; Ika Febrilia (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2021)
The purpose of this study was to examine the effect of country-of-origin and brand image on purchase intention through perceived quality as a variable intervening. The approach used in this research is a quantitative approach and data collection methods using survey method. Respondents in this study were students of the State University of Jakarta who had or are currently using Oppo smartphone. Where, in this study, 216 respondents were obtained from various faculties at the State University of Jakarta. The processed data is then used to test seven hypotheses using Structural Equation Modeling (SEM). The results of this study are: first, country-of-origin has a positive and significant effect on perceived quality; second, brand image has a positive and significant effect on perceived quality; third, country-of-origin has no significant effect on purchase intention; the fourth, brand image has no significant effect on purchase intention; fifth, perceived quality has a positive and significant effect on purchase intention; sixth, perceived quality can be a mediating variable on the relationship between country-of-origin and purchase intention; seventh, perception quality can be a mediator variable on the relationship between brand image and purchase intention. Keywords: Country-of-Origin, Brand Image, Perceived Quality, Purchase Intention, Oppo Smartphone